Mientras tanto - Makilan, Marielle delos Reyes 1999; Arumpac, Adjani G. (Quezon City College of Mass Communication, University of the Philippines, 2023)
Mientras tanto is a queer folk narrative following a defeated, nine-year-old Sol, in her pursuit of companionship after experiencing heavy bullying because of her nonconformity. When she almost gives up after the whole summer trying and failing to find new friends, she meets Talonon, a forest spirit, on her tenth birthday, who she would instantly connect and spend the remaining days of the summer with, aiding her recovery and healing.

The film is an inquiry on the ideal world for the Filipino queer child-- on practices, institutions, socioeconomic conditions, and how these interact and impact upbringing-- the hallmark of Queer Marxism, and an attempt to challenge Gender Performativity's regard for behaviors and the individual. The wishful nature of the ideal as a potential reality propels the film to maintain a familiar, realistic loo, towards which visual elements of magic realism intrude in the form of two-dimensional animations. Such realism recognizes that the world of mientras tanto is a reality to be struggled for, and that the visual antitheses in the form of animations are the gaps to be filled in this pursuit of the ideal. The subtlety of magic reflects the fragility of what needs to be changed, closing in the space between today's reality and tomorrow's ideal.
Vita.
Thesis
Includes bibliographical references (page 87) and appendices (pages 88-125).
Keywords: Short films; Gender identity in children -- Philippines .; Folklore -- Philippines